2017
DOI: 10.1007/s13595-017-0667-5
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy modelling and mapping soil moisture for observed periods and climate scenarios. An alternative for dynamic modelling at the national and regional scale?

Abstract: Key message Average soil moisture was spatially modelled for observed periods and climate scenarios using a fuzzy logic approach. Accordingly, a significant decline of soil moisture until 2070 in Germany and the Kellerwald National Park could be evidenced for soils influenced by ground water and by stagnant water and at sites on steep slopes and on southerly slopes. Context Soil moisture is an essential environmental factor affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In Germany, more and longer periods without precipitation are expected in the future [5]. In many studies, an increase in irrigation demand in different parts of the country is identified for the future [6][7][8][9][10][11]. As a result, improving water use efficiency through irrigation management and adopting advanced irrigation technology has become crucial and is considered one of the key adaption measures [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, more and longer periods without precipitation are expected in the future [5]. In many studies, an increase in irrigation demand in different parts of the country is identified for the future [6][7][8][9][10][11]. As a result, improving water use efficiency through irrigation management and adopting advanced irrigation technology has become crucial and is considered one of the key adaption measures [9].…”
Section: Introductionmentioning
confidence: 99%